Unmarriageable : a novel - Soniah Kamal (New York : Ballantine Books, 2019)
"In this retelling of Pride and Prejudice set in modern-day Pakistan, Alys Binat has sworn never to marry--until an encounter with one Mr. Darsee at a wedding makes her reconsider. A scandal and vicious rumor in the Binat family have destroyed their fortune and prospects for desirable marriages, but Alys, the second and most practical of the five Binat daughters, has found happiness teaching English literature to schoolgirls. Knowing that many of her students won't make it to graduation before dropping out to marry and start having children, Alys teaches them about Jane Austen and her other literary heroes and hopes to inspire them to dream of more. When an invitation arrives to the biggest wedding their small town has seen in years, Mrs. Binat excitedly sets to work preparing her daughters to fish for eligible--and rich--bachelors, certain that their luck is about to change. On the first night of the festivities, Alys's lovely older sister, Jena, catches the eye of one of the most eligible bachelors. But his friend Valentine Darsee is clearly unimpressed by the Binat family. Alys accidentally overhears his unflattering assessment of her, and quickly dismisses him and his snobbish ways. But as the days of lavish wedding parties unfold, the Binats wait breathlessly to see if Jena will land a proposal--and Alys begins to realize that Darsee's brusque manner may be hiding a very different man from the one she saw at first glance"--
Keywords: FICTION / Contemporary Women; FICTION / Family Life; FICTION / Literary